A previsão contratual de aplicação dos métodos extrajudiciais de solução de conflitos no contrato de convivência e pacto antenupcial - Rius, Carolina Eichemberger (2021)
This work deals with the provision of extrajudicial means of conflict resolution in the prenuptial agreement and in the coexistence contract, analyzing the formalities required for the drafting of contracts, as well as the aspects and characteristics of the ways to resolve disputes beyond the Judiciary. It demonstrates the brief historical evolution of the family and marriage in order to help understand the main theme. It analyzes the legal business developed by the couple before marriage or by the cohabitants in face of a relationship qualified as a stable union, which aims first of all to institute rules about the couple's assets. It concepts and presents the legal nature of the prenuptial agreement and coexistence contract and highlights their importance as a tool for the prevention of conflicts in the scope of family law, emphasizing, then, their social and legal usefulness. It presents the various forms of conflict resolution and its main characteristics. It also discusses the essential elements, both subjective and objective, of the methods, aiming to point out the possibility of pertinence of their application in relation to the disputes arising from the end of marriage and stable union. Discusses the possibility of linking the contractors to the clause that stipulates the solution of future disputes to the specific form of solution